The role of the Constitutional court for the protection of the human rights - Georgieva, Rayna (Law Journal of New Bulgarian University, 2022)
Today in Europe there is a complex system of protection of individual rights based on different sources of law and respectively with a different procedure for their defence, but with common constitutional legal root. The “catalogue” of basic rights in constitutions served as inspiration for the drafters of the International act in the field of human rights, whilst in the constitutional legislative process usually the legislator turns to the established International Human Rights Standards. Constitutional courts participate in the promotion and development of human rights standards through their case-law. The references in the past 30 years, the amendments of chapter eight of the Constitution and the case-law of the Constitutional court of the Republic of Bulgaria show that it has a roles as human rights court. However, the system of constitutional review could be improved with the facilitation of the ordinary courts in the direct application of the Basic law on cases. One of the possible measures is the legal education in the field of human rights protection and the availability of scientific legal publications in service of the practicing lawyers.